THE ROLE OF MAJELIS TA'LIM RUSYDATUL AZIZAH IN OVERCOMING QURAN ILLITERACY IN EARLY CHILDHOOD IN SIBANGGOR TONGA VILLAGE, MANDAILING NATAL REGENCY - Azizah, Rahmah; Lahmuddin, Lahmuddin (Universitas Al-Hikmah Indonesia, 2024)
Rusydatul Azizah is one of the ta'lim assemblies that has great potential to overcome Quran illiteracy in childhood. With non-formal education, Majelis Ta'lim Rusydatul Azizah can be an effective place to improve Quran literacy from an early age. The purpose of this study is to examine and analyze the role of Majelis Ta'lim Rusydatul Azizah in overcoming the problem of Quranic illiteracy in early childhood in Sibanggor Tonga Village, Mandailing Natal Regency. Child illiteracy poses a serious challenge to the development of community education, and Majelis Ta'lim Rusydatul Azizah is considered a non-formal institution that focuses on Islamic religious education and daily life. This research was conducted at Majelis Ta'lim Sibanggor Tonga Village from February 7-18, 2024. The method used in this research is qualitative method. The result of this research is the role of the Ta'lim Assembly in overcoming Quran illiteracy in early childhood by using the Baghdadiyah method, the Tilawati method and the Qiroati method to help and overcome Quran illiteracy in early childhood. Rusydatul Azizah's students are divided into 2 parts, namely: Juzz Amma and the Quran. The Tilawati method focuses on Bayati Rhythm. Qiroati method by pronouncing the memorization in reading the Quran in accordance with tajweed. The inhibiting factors experienced during the program are the lack of enthusiasm and motivation of students, excessive joking that can lead to unconducive during the learning process.